A CRIMINOLOGICAL STUDY OF PEDOPHILIA CRIMES IN THE JURISDICTION OF THE BALI POLICE FORCE - Saraswati, Putu Sekarwangi; Sudiana, A.A. KT.; Susrama, I Nengah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Sexual crimes nowadays do not only occur to adult victims, but also to children. Of course this will endanger the growth and development of children as the next generation of the nation. In order to prevent pedophilia cases against children, families and all levels of society play an active role in paying attention, protecting and protecting from treatments such as discrimination, exploitation, neglect, cruelty and injustice. The purpose of this study is to provide countermeasures taken to prevent the crime of pedophilia against children in Bali. Assistance for children in the examination process at the police until trial in court is expected to be able to improve the child's mentality and reduce the psychological impact of the pedophilia case that befell him. The research method used is empirical legal research method, the data processing and analysis used in this research is qualitative analysis. The final results of this comprehensive study are formulated to determine and analyze the factors causing the rampant crime of pedophilia and its implications for child victims, especially in the jurisdiction of the Bali Police as well as the obstacles faced in handling pedophilia cases.